2010
DOI: 10.1002/mnfr.201000147
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant effectiveness of coffee extracts and selected constituents in cell‐free systems and human colon cell lines

Abstract: The results emphasize that both original constituents and roast products contribute to the cellular antioxidant effectiveness of coffee.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(59 citation statements)
references
References 45 publications
3
54
0
2
Order By: Relevance
“…Bakuradze et al (2010) reported that ROS production was reduced by pre-incubating HT-29 cells with Arabica and Robusta filter coffee brews, and explained this capacity by the presence of 5-caffeoylquinic acid (5-CQA) and thermal degradation products. In line with this, many studies have shown the potential of 5-CQA for 14 decreasing ROS induced by hydrogen peroxide (Cho et al, 2009;Pavlica and Gebhardt, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bakuradze et al (2010) reported that ROS production was reduced by pre-incubating HT-29 cells with Arabica and Robusta filter coffee brews, and explained this capacity by the presence of 5-caffeoylquinic acid (5-CQA) and thermal degradation products. In line with this, many studies have shown the potential of 5-CQA for 14 decreasing ROS induced by hydrogen peroxide (Cho et al, 2009;Pavlica and Gebhardt, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, we have reported that spent coffee grounds obtained from the most common coffeemakers used at domestic and cafeterias levels (filter and espresso), and in less proportion from plunger (French press) ones, have antioxidant capacity because of the presence of relevant amounts of hydrophilic bioactive compounds, such as caffeoylquinic acids, mainly dicaffeoylquinic acids, and caffeine (Bravo et al, 2012). Because some of these coffee compounds have shown protective effects against oxidation (ROS formation) and DNA damage in human cell models when they were evaluated individually (Bakuradze et al, 2010;Cho et al, 2009;Faustmann et al, 2009;Pavlica and Gebhardt, 2005) or in coffee matrices (instant or coffee brew) in human cell models both directly or in interventional studies (Bakuradze et al, 2010;Bichler et al, 2007;Del Pino-García et al, 2012;Hoelzl et al, 2010); we hypothesize that aqueous spent coffee extracts might have antioxidant and genoprotective effects in human cells. However, up to now, the effect of these coffee by-products on oxidation and DNA damage in cells is still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The applicant provided two animal (Paur et al, 2010;Vicente et al, 2014) and two in vitro studies (Bakuradze et al, 2010;Boettler et al, 2011) in support of a mechanism by which coffee C21 could exert the claimed effect.…”
Section: Mechanism By Which the Food Could Exert The Claimed Effectmentioning
confidence: 94%
“…Specifically, kahweol and cafestol act by decreasing reactive oxygen species generation, prevention of DNA damage, and increased removal of superoxide radicals [21]; the major chlorogenic acid, 5-caffeoylquinic acid, reduces reactive oxygen species generation; and N-Methyl-2-methylpyridinium-iodide protects against DNA damage [22].…”
Section: Health Bene Ts Of Co Ee In Diabetesmentioning
confidence: 99%